2019
DOI: 10.1177/1069072719831975
|View full text |Cite
|
Sign up to set email alerts
|

Career Indecision Profile–Short: Reliability and Validity Among Employees and Measurement Invariance Across Students and Employees

Abstract: While the Career Indecision Profile–Short (CIP-Short) has demonstrated sound reliability and validity as a brief measure of career indecision in students, its psychometric performance in employees remains unclear. To facilitate research and practice on career indecision within the employee population, the present study examined the internal consistency reliability, structural validity, and convergent validity of the CIP-Short in employees. Additionally, the present study examined the measurement invariance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(139 reference statements)
0
14
0
3
Order By: Relevance
“…Although employees likely have more career experiences than college students, ambiguity management could still be relevant for employees' career decision‐making because ambiguity is an inevitable component of career decision‐making and can be hardly eliminated (Savickas et al, 2009; Xu & Tracey, 2016). Research has also shown that ambiguity aversion was positively associated with career indecision in the employee population (Xu, 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…Although employees likely have more career experiences than college students, ambiguity management could still be relevant for employees' career decision‐making because ambiguity is an inevitable component of career decision‐making and can be hardly eliminated (Savickas et al, 2009; Xu & Tracey, 2016). Research has also shown that ambiguity aversion was positively associated with career indecision in the employee population (Xu, 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…Ambiguity aversion plausibly mediate the links from childhood unpredictability and poverty to all four difficulty factors because childhood adversity can instill fear and anxiety about ambiguity in career decision-making, and such fear and anxiety can impede handling general anxiety, committing to a career choice, engaging in the decision-making process fully, and handling conflicting perspectives on career paths. Research has found that ambiguity aversion positively predicts all four factors of career decision-making difficulty, supporting the potential mediation of ambiguity aversion in the links between childhood adversity and all four factors of career decision-making difficulty (Xu, 2020b(Xu, , 2020c).…”
Section: Ambiguity Aversion With Career Decision-making Difficultymentioning
confidence: 80%
“…Освен тоа, кариерната неодлучност може да биде придружена со вознемиреност и недоволна мотивираност за надминување на тешкотиите што може да доведе до нарушување во развојот на кариерата, особено во периодот на адолесценција (Kelly & Lee, 2002) кога младите се соочуваат не само со вокациските задачи, туку и со голем број други значајни развојни предизвици (Шкариќ, 2009). Впрочем, неодлучноста во изборот на кариера, или попрецизно изборот на вид на образование или изборот на занимање кај младите е опсежно истражувана, но од друга страна, недостасуваат емпириски податоци за оваа појава кај веќе вработени (Xu, 2020).…”
Section: филозофски факултет скопјеunclassified